Determination and Prioritization of Public Library Services in Disasters - Yaghoub Norouzi; hamidreza Radfar; Nayereh Jafarifar (نشریه مطالعات دانش‌پژوهی)
Purpose: This study aims to identify and prioritize the services provided by public libraries during disasters, focusing on their roles before, during, and after such events.Methodology: The research, applied in purpose and descriptive-survey in method, utilized the fuzzy Delphi technique and the Best Worst Method (BWM) to analyze the opinions of 62 public library librarians and 11 library science experts in Iran.Findings: The resulting model outlines 33 services categorized into pre-disaster (14 services), during-disaster (12 services), and post-disaster (7 services). Services during disasters were deemed the most critical, followed by pre-disaster and post-disaster services. Key services include implementing mobile health ambassador libraries, forming voluntary campaigns among librarians, and establishing specialized groups to assess immediate library needs.Conclusion: Public libraries hold a vital role in disaster response and recovery due to their mission of equal access and community support. This study proposes a localized, actionable model of library services to enhance disaster management in Iran.Value: By addressing the unique needs of communities during crises, public libraries can significantly contribute to disaster preparedness and recovery, reinforcing their role as safe havens and resource hubs.